Accountability and Security in the Cloud First Summer School, Cloud Accountability Project, A4Cloud, Malaga, Spain, June 2-6, 2014, Revised Selected Papers and Lectures - Felici, Massimo; Fernández-Gago, Carmen (Security and Cryptology, 2015)
Cloud computing is a key technology that is being adopted progressively by companies and users across different application domains and industries. Yet, there are emerging issues such as security, privacy, and data protection. The First A4Cloud Summer School has been one of the first events in the area of accountability and security in the cloud. It was organized by the EU-funded A4Cloud project, in collaboration with the European projects CIRRUS, CocoCloud, CUMULUS, and SPECS. The 13 contributions included in this volume cover the state of the art and provide research insights into the following topics: accountability in the cloud; privacy and transparency in the cloud; empirical approaches for the cloud; socio-legal aspects of the cloud; cloud standards; and the accountability glossary of terms and definitions.